(untitled) (Nordic Journal of African Studies, 2008)
This paper reviews the role of language in addressing issues of instruction and diversity towards the achievement of the aims of basic education in Botswana. It also examines the role of the mother tongue in instruction in promoting and sustaining national educational and social goals. It further reviews the Botswana language in education policy and its implementation. The failures, inconsistencies between policy and practice, and other obstacles are discussed. The need for compromise in the implementation of mother tongue instruction in bilingual education model and its implications for literacy are discussed. Finally, suggestions for implementation of mother tongue instruction and model are outlined to ensure that government responds to the needs of her citizens, in the continuous efforts at mobilizing the people for national unity and sustainable development.